Single Dose Antibiotic Prophylaxis in Outpatient Oral Surgery Comparative Study - Y. Alhamdani, Fadia; Y.Alhamdani, Faaiz (Iraqi Journal of Pharmaceutical Sciences, 2017)
It is clear that correct application of antibiotic prophylaxis can reduce the incidence of infection resulting from the bacterial inoculation in a variety of clinical situations; it cannot prevent all infections any more than it can eliminate all established infections. Optimum antibiotic prophylaxis depends on: rational selection of the drug(s), adequate concentrations of the drug in the tissues that are at risk, and attention to timing of administration. Moreover, the risk of infection in some situations does not outweigh the risks which attend the administration of even the safest antibiotic drug. The aim of this study was to compare between 2 prophylactic protocols in out patients undergoing oral surgical procedures. Thirty patients, selected from the attendants of oral surgery clinic in Al-Karamah Dental Center, were subjected to different oral surgical procedures under local anesthesia. These patients were given single dose antibiotic prophylaxis in 2 groups; 1st group were 15 patients given 1 million i.u. of procaine penicillin I.M. 30 minutes before oral surgery, 2nd group were 15 patients given 600mg clindamycin orally 1 hours before oral surgery. The maximum time for all procedures was 2 hours. There was no difference between procaine penicillin (1 million i.u.), and clindamycin (600mg), regimens concerning post operative infection in out patient’s oral surgical procedures.Key words: Antibiotic prophylaxis, outpatient oral surgery